(untitled) (Perner’s Contacts, 2012)
The history of industrial development was in every stage connected with managerial changes. Future changes might be the change of environment, the change of customers and the change of competition. All these changes will cause quite a different future development of management. The time of looking for new opportunities through information technologies for businesses is coming. New organisations must be able to manage the new opportunities. Technology has been changing the traditional role of an engineer. Technologic operations as designs, prototypes, and manufacture of products, communication services, transportation, shipping, and forwarding have to provide results in a fraction of time. Recent progress in computer and information technology can facilitate the coordination of all activities. For this reason, an engineer must take a broader role in a business; otherwise, he will be in the position of a mere technician. Changes brought by the global economy thus require students to be systematically prepared for taking roles that are more complex at the beginning of their careers.